IDENTIFIKASI JENIS HAMA DAN PENYAKIT PADA TANAMAN BALANGERAN (Shorea balangeran Korth.): Identification of Pest and Disease in Plant of Shorea blangeran (Korth) Burck. - Reni Rahmawati; Eritha Kristiana Firdara; R. Setiadi (HUTAN TROPIKA, 2021)
This study aims to determine the types of pests and diseases, the level of damage,frequency and intensity of attacks on Shorea balangeran (Korth) Burck in the nursery areaof CV. Indonesian Agroforestry. The procedure of this research started from makingresearch plots, sampling, field and laboratory observations and data analysis. The resultsshowed that 44 balangeran seedlings were attacked by pest of grasshoppers (Valanganigricornis) and 83 were attacked by leaf spot disease of fungus Pestalotia sp.,Colletotrichum sp. and Phomopis sp. The frequency of pest attacks on balangeran is 11%and the intensity of attacks is 2.35% which includes the level of light damage. Theintensity of disease attacks on balangeran is 4.5% with a light damage level and an attackfrequency of 17.75% which is included in the light damage level. The intensity andfrequency of attacks for the combination of pests and diseases are 0.4% and 2% which areincluded in the level of light damage.Keywords: Diseases, pests, Shorea balangeran, agroforestry